Huaqiao dan Huaren: Sebuah Tinjauan Historis - Seda, Joanessa M.J.S (Paradigma: Jurnal Kajian Budaya, 2012)
This paper talks about the history of the birth and development of the terms Huaqiao and Huaren, the popular terms in Chinese for Chinese people who migrated out of China. In fact, there were two important factors which influenced the birth and development process of these terms. Those were the migration of the Chinese people out of China and the political development in and outside China. Without migration, these terms would not exist. Even if they exist, the birth and development of their meaning were influenced by the perceptions of all people who were involved and had interest in this migration process. These perceptions would not exist without the influence of the political condition and situation in and outside China. It is these factors which bring the terms Huaqiao and Huaren to its present meaning.